Interação humano-tv digital (IHTVD) e interatividade - Bizelli, José Luís [UNESP]; Souza, Maicon Ferreira de [UNESP] (My University, 2011)
With the development of Digital TV, the equipments are becoming more and more modernized in order to popular- ize the information that soon might reach all Brazilian families. That way, we open a space for discussion about the many directions that the usability applied on ISDB-Tb interactivity (Brazilian System of Digital Television) can take. This paper approaches the questions connected to the concept of usability and also the subjects related to the life cycle of some technologies (existence time, obsolescence) Also talks with the definition of interactivityon Digital Television since it is responsible for the emergence of a new contingent of interacting people which goes from the computer and portable equipments users to the passive TV viewers. It’s possible to conclude that the Human-Digital TV Interaction (HDTVI) comprehends the synergy between three actants on Digital TV: the col- lective (or not) TV viewer; the interface and the issuer who can be represented by an Artificial Intelligence (AI) service.

Com a implantação da Televisão Digital, cada vez mais os equipamentos se modernizam para atender às demandas pela democratização da informação que deve chegar a todas as residências brasileiras. Abre- se, assim, um espaço para a discussão sobre as diversas direções que pode tomar a usabilidade aplicada à interatividade do ISDB-Tb (Sistema Brasileiro de Televisão Digital). O presente trabalho aborda, além das questões ligadas ao conceito de usabilidade, os temas relacionados com o ciclo de vida das tecnolo- gias – tempo de existência e obsolescência –, trabalha a definição da interatividade na Televisão Digital à medida que ela é responsável pelo surgimento de um novo contingente de interagentes que abrange tanto os usuários de computadores e aparelhos portáteis quanto os simples telespectadores passivos. É possível concluir, portanto, que a Interação Humano-TV Digital (IHTVD) compreende a sinergia entre os três ac- tantes da televisão digital: o telespectador coletivo ou não; a interface apresentada; e o emissor, que pode ser representado por um serviço de Inteligência Artificial (IA).
Keywords: Digital Television; Interaction Human-Digital TV; Usability; Inovação tecnológica; TV digital; interatividade